Administrative Pitfalls in Gender Mainstreaming Practices: Learning from 3 districts: Jepara Regency, Pati Regency and Pemalang Regency - Mayadina Rohmi Musfiroh; Ahmad Fauzan Mubarok (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The gender mainstreaming (GM) policy was released 24 years ago. However, on the way, it still has not had a significant impact on the realization of gender equality and justice. In fact, in many cases, there has actually been an increase in violence against women and children in Indonesia. This article aims to explore the context behind the birth of regulations on gender mainstreaming in three districts (Pemalang, Pati, and Jepara) and to examine the effectiveness of the implementation of gender mainstreaming in the three districts. This article uses qualitative methods and field research. This article reveals several findings, including; First, the biggest challenge in implementing gender mainstreaming lies in the commitment and capacity of system actors in gender mainstreaming in each district; Second, the commitment of policymakers has not been accompanied by effective implementation and monitoring and evaluation. Therefore, it is necessary to bridge commitments, regulations, and policy implementation so that the implementation of gender mainstreaming is not trapped in formalities and even tends to be normative-administrative. More than that, gender mainstreaming must have an impact on gender equality and justice, disability, and inclusivity in society with its original goal.